THE EFFECT OF TOXIC LEADERSHIP AND JOB STRESS ON TURNOVER INTENTION IN LOGISTIC COURIER BEKASI CITY - Febrisi Dwita (Airlangga Journal of Innovation Management, 2022)
This study aimed to examine the effect of toxic leadership on turnover intention, toxic leadership on job stress, and job stress and turnover intention. These study populations are three logistics companies engaged in logistics in Bekasi. This study uses a non-probability purposive sampling technique. For a sample of 105 respondents from operational units in logistics courier companies, the determination is based on (Hair et al., 2017), but only 99 respondents complete questionnaires are considered usable. Data analysis using SEM with Smart PLS software. The results show a positive and significant direct relationship between toxic leadership and employee job stress, and there is a positive and significant direct relationship between work stress and turnover intention. Still, there is no negative relationship between toxic leadership and turnover intention. In addition, there are new findings in a study conducted on employees of the operational division of a logistics company located in the city of Bekasi. The higher application of toxic leadership by the leader to employees does not affect the intensity of turnover intention to be carried out by the employee. It is because the intention to move is felt by employees based on internal factors, namely work stress, not from the negative leadership style of their superiors. Further research is expected to use mediating variables with job satisfaction and physical work environment on turnover intention. It is also expected to be able to use qualitative methods for a better comparison of research results. It is also hoped that further research will be able to further refine this research by adding research subjects and other variables that might affect turnover intention so that further research can be more developed and varied and produce conclusions from more comprehensive research.